Water and energy use efficiency in the production of tomato under different water conditions - Henrique Maldonado da Silva, Lucas; Rezende, Roberto; Felipe Barion Andrean, André; Soares Wenneck, Gustavo; de Souza Terassi, Daniele; Crepaldi de Faria Nocchi, Raiana; Villa e Vila, Vinícius (Comunicata Scientiae, 2023)
The efficient use of water and energy is fundamental to a sustainable agricultural practice. Deficit irrigations can contribute to saving water and energetic resources. This work aimed at analyzing the influence of water reposition in the water and energy efficiency use for growing tomato cocktail type tomato. The experiment was conducted in vegetation house, and the randomized design was adopted with five levels of water reposition (25, 50, 75, 100 and 125% of evapotranspiration in culture (ETc)) and six repetitions. The morphological contents were evaluated (number of bunches, number of abortions, fresh mass of aerial part, stem diameter and height), SPAD index (Soil Plant Analysis Development), water demand, productivity, energy use and energy productivity. Data were analyzed through variance analysis, average comparison, regression analysis and correlation. Water deficit affects growth, development and productivity of cocktail type tomato. The morphological development and the production yield show high correlation with water availability. The water replacement of 75% of ETc has shown better efficiency in water and electricity use in growing cocktail type tomato.